Circumpolar Deep Water and Shelf Sediments Support Late Summer Microbial Iron Remineralization. Issue 11 (7th November 2021) - Smith, Abigail J. R.; Ratnarajah, Lavenia; Holmes, Thomas M.; Wuttig, Kathrin; Townsend, Ashley T.; Westwood, Karen; Cox, Martin; Bell, Elanor; Nicol, Stephen; Lannuzel, Delphine
Abstract: Despite widespread iron (Fe) limitation in the Southern Ocean, intense phytoplankton blooms are observed around productive coastal regions such as the Mertz Polynya (off George V Land and Adelie Land, East Antarctica; 140–155°E). Sources of Fe across coastal East Antarctica vary, with limited data available for late summer months. We investigated the sources of dissolved Fe (dFe; <0.2 μm) at 19 oceanographic stations in the Mertz Glacier Region (64–67°S; 138–154°E), between January and March of 2019. Concentrations of dFe ranged from below detection limit (0.03 nM) at the surface, to 0.34 nM above the base of the mixed layer (35 m), reaching 0.59 nM at depth (520 m). Using oceanographic features and trace element ratios (manganese and titanium), we identified Circumpolar Deep Water (CDW) and shelf sediment resuspension in modified CDW as contributors of dFe to the region over this period. Microbial Fe remineralization was evident where nutrient‐rich water met highly oxygenated waters over the continental shelf. Reduced Fe concentrations in the mixed layer and euphotic zones suggested rapid biological uptake prior to sampling. Despite proposals for pelagic Fe recycling by marine animals, preliminary investigations reveal no significant spatial relationship between animal presence and surface ocean Fe concentrations over the study area. Further research is required to identify seasonal changes to Fe supply in coastal areas which will strengthen our understanding of the Fe cycle and its influence on microbial and primary productivity in this globally significant region. Key Points: Circumpolar Deep Water and sediment resuspension supply iron to the Mertz Glacier Region during late summer Significant iron remineralization occurs over the continental shelf as a result of bacterial production The presence of marine animals show no observable relationship with dissolved iron distributions in surface waters